BUILDING YOUNG RESEARCHERS’ COMPETENCE THROUGH MODERN DATA PROCESSING APPLICATION TO ENHANCE EDUCATION QUALITY - Wirologo, Haryo Kuncoro; Nasution, Hafifah; Handarini, Dwi; Kartikowati, Rr. Sri; Hidayat, Nurdin (International Journal of Engagement and Empowerment (IJE2), 2024)
Data analysis techniques are one of the critical stages that young researchers must carry out when conducting research. Apart from that, young researchers also need to understand knowledge related to statistical methods to make carrying out their research easier. This community service activity aims to increase the knowledge of young researchers (especially students) related to Structural Equation Modeling using the PLS and the Simultaneous Equation Model. Apart from that, this activity also aims to increase the experience of young researchers by directly instilling the use of the SmartPLS program. This Community Service Activity was conducted as a seminar on June 13, 2024, from 08.00 to 12.00 WIB (09.00 to 13.00 MST) online via Zoom Cloud's Meeting. Universiti Malaysia Sabah is a partner in this activity. Seventy-six participants, including lecturers, students, and researchers from state and private universities in Indonesia and Malaysia, participated in this activity. The activity evaluation results show that participants' understanding and skills regarding Structural Equation Modeling-Partial Least Square (SEM-PLS), SmartPLS, and Simultaneous Equation Model have increased